2015
DOI: 10.5530/jyp.2015.3.5
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Department – A Prospective Study at a Tertiary Care Teaching Hospital

Abstract: Objective: To assess prevalence and pattern of off-label and unlicensed use of drugs in paediatric outpatient department. Methods: In this prospective study, children attending paediatric outpatient department of a tertiary care teaching hospital were enrolled. Demographic data, clinical history and completeprescription given to the patient were noted. Prescriptions were analysed for off-label and unlicensed drug use with the help ofrecent British National Formulary for Children (BNFC) and National Formulary o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
4
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 19 publications
4
4
1
1
Order By: Relevance
“…A study published by Bhadiyadara et al reported that out of 405 drugs, 10.1% drugs were used in an off label manner as per BNFC-2012. [9] Though their study was comparable to a previous outpatient study reported a decade back from UK which showed 10.5% offlabel prescription according to BNFC-1998, [10] our study identified a higher proportion of off-label drugs (27.9%) as per BNFC 2016-2017, which suggests the improvement in quality of the database due to periodic editions that reflect ever emerging clinical practices. Turner et al, studied drug use conditions in a PICU, published that 70% of the total patients received at least one off label drug and their percentages are similar to the findings of our study.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…A study published by Bhadiyadara et al reported that out of 405 drugs, 10.1% drugs were used in an off label manner as per BNFC-2012. [9] Though their study was comparable to a previous outpatient study reported a decade back from UK which showed 10.5% offlabel prescription according to BNFC-1998, [10] our study identified a higher proportion of off-label drugs (27.9%) as per BNFC 2016-2017, which suggests the improvement in quality of the database due to periodic editions that reflect ever emerging clinical practices. Turner et al, studied drug use conditions in a PICU, published that 70% of the total patients received at least one off label drug and their percentages are similar to the findings of our study.…”
Section: Discussionsupporting
confidence: 81%
“…These two databases were selected as Micromedex is known for Micromedex is a well known source that provides easy access to a large amount of FDA approved data and the BNFC is a standard compendia used by physicians across the globe. The mean age of the population in our study was lesser than that seen in other studies based on Off‐label drug use in pediatrics in India . This could be attributed to the fact that a large proportion of the total patients enrolled in the current study were in the age group 1 month–2 years as compared to the number of patients enrolled in age groups 2–12 years due to the higher frequency of diseases such as upper and lower respiratory tract infections, seizure disorders and acute gastroenteritis occurring in this population.…”
Section: Discussioncontrasting
confidence: 63%
See 3 more Smart Citations